Extracellular Vesicles Secreted by TDO2-Augmented Fibroblasts Regulate Pro-inflammatory Response in Macrophages - Peck, Kiel A.; Ciullo, Alessandra; Li, Liang; Li, Chang; Morris, Ashley; Marbán, Eduardo; Ibrahim, Ahmed Gamal (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) are secreted lipid bilayer vesicles that mediate cell to cell communication and are effectors of cell therapy. Previous work has shown that canonical Wnt signaling is necessary for cell and EV therapeutic potency. Tryptophan 2,3-dioxygenase (TDO2) is a target gene of canonical Wnt signaling. Augmenting TDO2 in therapeutically inert fibroblasts endows their EVs with immunomodulatory capacity including attenuating inflammatory signaling in macrophages. Transcriptomic analysis showed that macrophages treated with EVs from fibroblasts overexpressing TDO2 had blunted inflammatory response compared to control fibroblast EVs. In vivo, EVs from TDO2-overexpressing fibroblasts preserved cardiac function. Taken together, these results describe the role of a major canonical Wnt-target gene (TDO2) in driving the therapeutic potency of cells and their EVs.